Conjunctival flora in Behçet patients - Gündüz, Abuzer; Gündüz, Ayten; Cumurcu, Tongabay; Seyrek, Adnan (Elsevier B.V., 2008)
Background: To determine the difference in conjunctival flora in Behçet patients compared with the normal population. Methods: This study was carried out on a study group of 50 patients in the inactive period of Behçet's disease and a control group of 50 age- and sex-matched healthy subjects with no systemic or ocular disease. A swab was taken from the lower fornix using a sterile swab and inoculated into bloody eosin methylene blue, chocolate, and Sabouraud dextrose agar media. Results: The mean age was 36.04 (SD 2.16) years for the Behçet group and 35.64 (SD 1.96) years for the control group. Bacterial growth was observed in 92% (n = 46) of the Behçet group and 56% (n = 29) of the control group. The Behçet group results were Staphylococcus aureus in 12 (24%), coagulase negative staphylococci (CNS) in 32 (64%), Moraxella spp in 8 (16%), Streptococcus spp in 8 (16%), Bacillus spp in 4 (8%), Neisseria spp in 4 (8%), Candida spp in 3 (6%), and Haemophilus spp in 1 (2%). In the control group, the results were S. aureus in 2 (4%), CNS in 24 (48%), Moraxella spp in 2 (4%), Streptococcus spp in 1 (2%), Bacillus spp in 3 (6%), Neisseria spp in 3 (6%), and Candida spp in 1 (2%). Interpretation: S. aureus, Moraxelic spp, and Streptococcus spp colonization was significantly higher in the conjunctival flora of Behcet patients than in that of the control group. A bacterial etiology may be involved in the pathogenesis of Behcet's disease.
Keywords: Behçet's disease; Conjunctival flora; Ocular infection